Investigation on the mechanical properties and oil resistance of sulfur cured nitrile rubber/hydrogenated nitrile butadiene rubber blends. Issue 12 (1st October 2021) - Zou, Huimin; Jing, Yuanrong; Tu, Jieyun; Shi, Xinghui; Kadlcak, Jakub; Yong, Zhanfu; Liu, Susu; Liu, Guangyong
Abstract: Nitrile rubber (NBR)/hydrogenated nitrile butadiene rubber (HNBR) blends with various ratios were compounded with internal mixer and two‐roll open mill. Mechanical properties and low‐temperature performance (TR10) of the NBR/HNBR blends after aging under different conditions were investigated. Furthermore, equilibrium swelling test and moving die rheometer (MDR) test were used to systematically investigate the effects of HNBR dosage on the crosslink densities and curing behaviors. Vulcanization torque and crosslink densities decreased with an increase in HNBR content. The crosslink density of pure HNBR is higher than that of pure NBR, which is related to the macromolecular structures of the rubber. Compression sets of the NBR/HNBR vulcanizates were correlated with HNBR dosage indicating a linear relationship. Low‐temperature performance of the NBR/HNBR blends was improved after being aged in the synthetic hydrocarbon hydraulic oils (SH‐1 and SH‐2). This work shows that the low‐temperature performance and oil resistance could be better balanced by blending NBR with HNBR, while the mechanical properties maintain relatively high level. Abstract :